Pengaruh Penggunaan Media Sosial Dalam Pembentukan Akhlaq Dan Kepribadian Sosial Pada Siswa SMP Di Kota Depok - Khotimah Herliana; Asep Saepul Bahri (Journal on Education, 2024)
The development of social media is currently very massive and growing very rapidly, this will certainly have a significant impact on one's life. This is because everyone seems to be inseparable from the existence of social media, be it for the purposes of existence, or just to fill spare time. Social media certainly has a positive impact as well as a negative impact, especially on the development of students' akhlaq and personality. This is because at school age, especially at the junior high school level, which is an age of unstable mental development and is also in a period of self-discovery, social medical is always a reference in behavior. This is the basis for this research. This research was conducted on junior high school students in the city of Depok, with the method taken, namely a survey by taking data from respondents to find answers to existing problems. With correlation and percentage analysis techniques. From the results obtained, the effect of using social media on akhlaq learning is 45% negative, which means that excessive use of social media will certainly reduce students' understanding of akhlaq. In addition, the relationship between social media and social personality gets a value of r = 0.30, which means that the use of social media has a positive impact on social personality such as openness to peers even though it is not too dominant. And the relationship between akhlaq learning and social personality gets a value of r = 0.60, which means that tends to have good akhlaq of course the social personality will also be good.